Daya Tarik Gelombang Bono Sebagai Objek Wisata Unggulan di Kabupaten Pelalawan - Yuliarti, Rini; Syaputra, Doddy (Jurnal Daya Saing, 2015)
Abstract: The Travel Attractions Bono was amazing and unmatched so as to attract tourists to come to the District Pelalawan. For world surfers (surfers) and tourists from outside, Waves Bono Kampar is an amazing discoveries reveal even the world selencar remarkable for "Bono Kampar ". Bono first waves or wave Kampar River as a frightening figure, but now it become a mainstay for Palalawan Tourism and Riau Province. District Government strategy to develop tourism area Bono As a mainstay of tourism in Pelalawan had done well but not maximized. The strategy that has been done to develop the region are: Conducting regional cultural arts performances Bono, Bono waves Held promotional events, exhibitions Conducting tourism and tourism facilities and infrastructure. Keywords: Fascination, Attractions Bono